Long-term changes of stimulation intensities in hypoglossal nerve stimulation - Zhu, Zhaojun (J Clin Sleep Med, 2020)
STUDY OBJECTIVES: Hypoglossal nerve stimulation (HNS) is a novel therapy in the treatment of obstructive sleep apnea. Previous studies have focused on the effectiveness of HNS, but there are no studies specifically investigating the long-term changes of the stimulation intensities in HNS. Increasing stimulation intensity requirements have been reported in the past in other peripheral nerve stimulation therapies. The aim of this study was to investigate the development of stimulation intensities over the observation period of 4 years. METHODS: All patients who were implanted with an HNS system since December 2013 and maintained a bipolar configuration over the observation period were included. Sensation threshold (ST), functional threshold, the titrated stimulation intensity (SI), and the apnea-hypopnea index (AHI) were recorded. RESULTS: A total of 82 patients were enrolled (sex: 69 men, 13 women, age: 60 ± 11 years, body mass index: 29. 8 ± 4.0 kg/m(2)). Two months after surgery, the median ST was 0.8 ± 0.5 V. During the observation period of 48 months, no significant change of ST was observed. The median ST was 1.0 ± 0.4 V (P = 0.93) at 48 months. Similar results were found for functional threshold and the titrated stimulation intensity. There was a significant reduction of the baseline median AHI when compared with the median AHI at 1, 12, 24, 36 and 48 months after surgery (P < 0.05). CONCLUSIONS: The stimulation intensities in HNS show no significant changes over 4 years. Despite the constant stimulation intensity, AHI was significantly reduced. This indicates that the stimulation threshold of the hypoglossal nerve does not change over time with this therapy. CITATION: Zhu Z, Hofauer B, Wirth M, Heiser C. Long-term changes of stimulation intensities in hypoglossal nerve stimulation. J Clin Sleep Med. 2020;16(10):1775–1780.